Kepemimpinan Kepala Bagian Umum dan Keuangan Sekretariat Kabupaten Sidenreng Rappang - Hariyanti Hamid (JIA: Jurnal Ilmiah Administrasi, 2012)
The goal of this research was to determine the leadership style ofHead of General and Financial Section of Sidenreng RappangRegency Office along with all influencing factors. The populationincludes forty-eight staffs of General and Financial Section. Themethods used to collect data were observation, interview,questionnaire, and literature study. Then those data analyzed usingstatistical-descriptive analysis.The result shows various leadership style of Head of General andFinancial Section: autocratic (by 6,25%), militarystic (by 0%),patternalystic (by 8,33%), charismatic (by 87,50%), and democratic(by 89,58%). While the leadership style includes education level, jobexperience and timeline, good physical health, ability of emotioncontrol, high intelligency, and good personal being.